2017
DOI: 10.1007/s12649-017-0101-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Optimization of Macroalgae-Derived Solid Acid Catalysts

Abstract: Solid acid catalysts were synthesized from macroalgae Sargassum horneri via hydrothermal carbonization followed by sulfuric acid sulfonation. A three-variable Box-Behnken design and optimization was used to maximize surface acidity. The optimal preparation conditions were found to be at the carbonization temperature of 217 °C, the carbonization time of 4.6 h and the sulfonation temperature of 108.5 °C. Under these conditions, the highest surface acidity achieved was 1.62 mmol g −1 .Physical and chemical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…The same authors also showed that by addition of 50% acrylic acid during the hydrothermal treatment materials with 2-fold-enhanced COOH (2.88 mmol/g) and 1.2-fold-enhanced SO 3 H densities (1.53 mmol/g) were produced . Similarly, sulfonation of hydrothermally treated macroalgae produced sulfonated hydrochars with the concentration of SO 3 H sites being around 0.953–1.62 mmol/g . The higher degree of SO 3 H functionalization achieved over lignin- and lignocellulose-based hydrochars is most likely due to the presence of a more aromatized carbon framework structure in comparison to the sugar-based hydrochars.…”
Section: Sulfonation Methodsmentioning
confidence: 88%
See 2 more Smart Citations
“…The same authors also showed that by addition of 50% acrylic acid during the hydrothermal treatment materials with 2-fold-enhanced COOH (2.88 mmol/g) and 1.2-fold-enhanced SO 3 H densities (1.53 mmol/g) were produced . Similarly, sulfonation of hydrothermally treated macroalgae produced sulfonated hydrochars with the concentration of SO 3 H sites being around 0.953–1.62 mmol/g . The higher degree of SO 3 H functionalization achieved over lignin- and lignocellulose-based hydrochars is most likely due to the presence of a more aromatized carbon framework structure in comparison to the sugar-based hydrochars.…”
Section: Sulfonation Methodsmentioning
confidence: 88%
“…The hydrochar-based sulfonated materials or sulfonated hydrothermal carbons (SHCs) have been successfully obtained by reacting hydrochars derived from glucose, , ,, xylose, , sucrose, cellulose, , as well as natural organic matter such as lignin, ,, wood meal, and macroalgae with a strong sulfonating agent (concentrated H 2 SO 4 , fuming H 2 SO 4 , and chlorosulfonic acid). These SHCs have been demonstrated to exhibit SO 3 H densities ranging between 0.57 and 1.58 mmol/g.…”
Section: Carbon Supports or Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characterization of the OMSC catalyst was carried using various analytical methods. The sulfonic and total acid densities were estimated by the titration method, as reported in several literature articles with a slight modification [ 27 , 35 , 48 , 59 ]. Briefly, 0.05 g of the catalyst was mixed with a 15 mL 2 M NaCl solution and stirred at room temperature for 1 h. After that, the filtrate was titrated with 0.05 M NaOH solution using phenolphthalein indicator, and the sulfonic acid (SO 3 H) density was determined as the amount of NaOH solution consumed.…”
Section: Methodsmentioning
confidence: 99%
“…Four independent variables used in sulfonation of the ICG were sulfonation time (X1), volume H2SO4 (X2), power level of microwave (X3), as well as stirring rate (X4). These 4 parameters were selected based on the most significantly variables influencing the catalytic activity as well as from previous study [9]. Table 1 tabulates experimental level coded and range for independent variables.…”
Section: Single Response Optimization For Yield (Y) and Conversion (C)mentioning
confidence: 99%